Middle Income Trap and Infrastructure issues In Indonesia: A Strategic Perspective - Setiawan, Sigit (International Journal of Economics and Financial Issues, 2017)
This study aims to analyze why (the urgency) and how (the process) Indonesia has been struggling - in formulating strategic policy framework and the implementation - to fix its lack of infrastructure problem, as part of its effort to boost its economic growth and become a high income country. The scope of study is limited to infrastructure only, one of the critical concerns in leading the way to be a high income country. The study adopts qualitative descriptive analysis method. Keywords : Economic Development, Fiscal Policy, Infrastructure JEL Classifications : F63, E62, H54